THE EFFECT OF JOHAR PLANT FLOWER EXTRACT “CASSIA SIAMEA” ON THE DEGREE OF PLASMODIUM BERGHEI PARASITEMIA IN VIVO - Pandango, Ivana Griselarosa Koni; Laksemi, Dewa Ayu Agus Sri; Sudarmaja, I Made; Diarthini, Ni Luh Putu Eka (E-Jurnal Medika Udayana, 2024)
Malaria is a disease caused by a parasite of the genus Plasmodium sp. that spreads through the bite of the female Anopheles mosquito. Malaria is still a global problem because almost half of the world’s population is at risk of malaria which is endemic to 86 tropical and subtropical countries. In addition, resistance to antimalarial drugs that occur in some places makes many researchers try to find antimalarial drugs made from natural ingredients so that they can reduce the risk of resistance with minimal effects. One natural ingredient that is thought to be used as an antimalarial drug is the johar flower (Cassia siamea). The objective of this study is to determine the effect of johar flower extract (Cassia siamea) at doses of 10 mg/kgBW, 100 mg/kgBW, and 1000 mg/kgBW on the degree of parasitemia in male mice Balb/c strain infected with Plasmodium berghei. This study is an experimental study in vivo using the design of the Randomized Post-test Only Controlled Group method using 24 samples of mice which were divided into four groups, one negative control group and three treatment groups. The average degree of parasitemia was obtained in the control group of 24.9%, the 10 mg/kgBW dose treatment group of 13.4%, the 100 mg/kgBW dose treatment group of 10.3% and the 1000 mg/kgBW dose treatment group of 12.2%. Based on the results of the analysis with One-way ANOVA, an average difference was found between the control and treatment groups with a p-value < 0.001. The result showed that giving johar flower extract (Cassia siamea) had an influence on antimalarial activity in reducing the percentage of parasitemia of mice infected with Plasmodium berghei by looking at the average difference between the control group and the treatment and obtained the average results of the treatment group of 100 mg/kgBW and 1000 mg/kgBW had the highest influence in reducing the degree of parasitemia.   Keywords: Cassia siamea, Antimalaria, Plasmodium  berghei, Degree of Parasitemia